2023
DOI: 10.1007/s11192-023-04792-5
|View full text |Cite
|
Sign up to set email alerts
|

On the culture of open access: the Sci-hub paradox

Abstract: Shadow libraries, also known as "pirate libraries", are online collections of copyrighted publications that have been made available for free without the permission of the copyright holders. They have gradually become key players of scientific knowledge dissemination, despite their illegality in most countries of the world. Many publishers and scientist-editors decry such libraries for their copyright infringement and loss of publication usage information, while some scholars and institutions support them, som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In 2022, indeed, Maddi and Sapinho reported surprising empirical findings concerning the open access citation advantage (OACA) . In detail, comparing the citation impact of 2,458,378 publications in fully OA journals to that of a control group of non-OA publications over the period 2010–2020, the team found that there is no OACA for publications in fully OA journals and that there is rather a disadvantage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, indeed, Maddi and Sapinho reported surprising empirical findings concerning the open access citation advantage (OACA) . In detail, comparing the citation impact of 2,458,378 publications in fully OA journals to that of a control group of non-OA publications over the period 2010–2020, the team found that there is no OACA for publications in fully OA journals and that there is rather a disadvantage.…”
Section: Resultsmentioning
confidence: 99%
“…Chemistry researchers should not naively assume that publishing in OA journals will automatically translate into increased citations, because Web sites such as Sci-Hub already make their research output published in the international literature openly accessible . It is more beneficial, in this respect, to “green” self-archive all published research articles in a personal academic Web site, thereby offering to colleagues interested in a research chemist’s work a complete and logically ordered outlook of one’s researcher activity.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of these control variables drew from the literature, considering their potential impact on received citations. These variables encompass the journal's impact factor, the number of countries involved in the publication (indicative of international collaboration) (Ni & An, 2018), the number of funders (Quemener et al, 2023;Yan et al, 2018), the publication's openaccess status (Maddi & Sapinho, 2023), the discipline of the publication (Lillquist & Green, 2010), and the publication year (Bornmann, 2013). These variables were integrated into the model to capture and control for potential effects on our dependent variable, citations.…”
Section: Adjustment Of Publons Datamentioning
confidence: 99%